Initial development and assessment of the soccer competence scale - Weiller-Abels, K.; Moore, E. W. (Research Quarterly for Exercise and Sport, 2018)
Background/Purpose: There are general competence measures available to assess youth`s cognitive development. One important measure is youth`s perception of their ability in relation to their peers. As youth develop cognitively, they develop the ability to differentiate between effort, luck, and ability (Nicholls, 1989). This ability is what opens the door for youth to develop an ego goal orientation in addition to a task goal orientation (Nicholls, 1989). Previous work in the academic and physical activity domains has shown that it is around the age of 13 that the majority of youth have a differentiated understanding of effort, luck, and ability. However, academic research has shown that students around the age of 10 are able to accurately rate their ability at a skill (i.e., math or reading) in relation to their peers. However, the majority of research into individuals` competence has been self-referenced in the physical domain, rather than relative to peers. Therefore, the Soccer Competence Scale was developed to measure players` perception of their ability in general and at specific components of soccer (e.g., offensive, passing, dribbling, defensive) in relation to their soccer peer group Method: Eight items were developed to assess youth`s soccer competence with the following response scale: Top 1-20%, 21-40%, 41-60%, 61-80%, and 81-100%. Male and female soccer players (N = 152, 62% female) participating in the Olympic Development Program for players 12-14 years of age were surveyed during their last training sessions of the year. Analysis/Results: The measure was shown to have high reliability (Cronbach`s Coefficient alpha = .96). The inter item correlationswere all moderate to high with values over .06. The mean response was 2.77 with a standard deviation of 1.33. More specifically, the younger girls` reported a mean competence rating of 2.08 compared to the older girls` rating of 3.28, which highlights the cognitive differentiation development occurring among the female players. However, the males, showed less clear pattern, with the younger boys` self-rating of 3.05 being slightly, though not significantly higher, than the older boys` self-rating of 2.45. Conclusions: This supports the point that players were ble to report their ability level in a distributed manner, versus all the players perceiving that they are in the top 1-40% (response value 1 or 2) of the peer group for all soccer skill components. Furthermore, the players` competence was significantly, positively correlated with their perception of a task-involving climate and their ODP coaches` competence, and not correlated with experiencing an ego-involving climate. These relationships align with Achievement Goal Perspective Theory for competence development in a taskinvolving climate. This measure can help examine soccer players` cognitive development by assessing their perceived ability in relation to their peers. Contact: Karen.Weiller@unt.edu